Development of an instrument to measure student’s self-efficacy level in mathematics learning - Nugraha, Wildan; Umam, Khoerul (SAINTIS Publishing, 2023)
The purpose of this research is to measure the level of students' self-efficacy by developing a mathematical self-efficacy instrument and to determine the quality of the developed instrument. This research is categorized as Research and Development (RD). The resulting product of the research is a questionnaire consisting of 28 statements. The development of the mathematical self-efficacy instrument was carried out using a formative research development model. The study was conducted in 11th-grade classes at SMA 90 in South Jakarta. The findings of this research indicate that the developed instrument is valid, reliable, and of reasonably good quality, as it passed the instrument testing stages. Additionally, this research also demonstrates the criteria for students' self-efficacy level using the developed instrument.